THE STUDY OF THE INTERACTION BETWEEN GOLD (III) AND 2-(3-AZEPAN-1-YL)-2-HYDROXYPROPYLTHIOACETIC ACID BY MEANS OF POTENTIOMETRIC AND AMPEROMETRIC TITRATION METHODS (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
The interaction of gold (III) with 2-(3-azepan-1-yl)-2-hydroxypropylthioacetic acid has been studied by means of potentiometric titration and amperometric titration methods. It has been shown that the given interaction possesses an oxidation-reduction character with further complex formation. The ratio of interacting substances (oxidizer : reducing agent) is 1:1. A possible scheme of interaction has been also suggested.
Keywords: potentiometric titration method; amperometric titration method